Workshop 6 report: Wider impacts of public transport and successful implementation of desirable and beneficial projects. (September 2018) - Venter, Christo; Leong, Wai Yan
Abstract: This paper synthesizes evidence from Workshop 6 'Wider impacts of public transport and successful implementation of desirable and beneficial projects' of the 15th International Conference on Competition and Ownership in Land Passenger Transport. The purpose of the workshop was to consider recent advances in identifying, understanding, and measuring the wider impacts of public transport, defined as those not typically included in assessments of direct user and system costs and benefits. While not all impacts are as yet well understood, progress is being made both conceptually and methodologically. A promising methodological convergence is apparent between disciplines dealing with different aspects of the social value of transport – for instance psychology and geography – and between different possibly overlapping definitions of wider impacts – such as accessibility, option value, and agglomeration benefits. The workshop also delved more deeply into the role of Cost-Benefit Analysis (CBA) and wider impact assessment in decision making. Case studies show that CBA does not inform decisions around project implementation as deeply as it might, and that assessments of wider benefits may open up space for manipulation of outcomes by vested interests. The workshop concluded that more work is needed on appraisal frameworks that are sufficiently transparent and rigorous to avoid abuse, and called for more case studies on the interaction between impact assessment and the political economy of institutions and decision makers.